The 2018 Luwu Regency Government Budget Policy and Its Implications for Village Development - William; Armin; Sukri (Awang Long Law Review, 2021)
This study aims to determine the cause of the delay in the process of determining the Regent's Regulation on the financial management of Village Fund Allocation (ADD) and Village Funds and to describe and analyze the 2018 Luwu Regency Government Budget Policy and its Implications for Village Development. This research was conducted in Luwu Regency. This type of research is qualitative. Descriptive approach to make a systematic, factual, accurate description, picture, or painting of the factors, properties, and relationships between the phenomena being investigated. Data were collected through in-depth interviews and literature review. The data were analyzed using policy theory, the concept of policy implications, the concept of regional financial management, and the concept of village development. The results showed the delay in the process of drafting and stipulating the Regent's. Regulation on Financial Management of Village Fund Allocation (ADD) and Village Funds in Luwu Regency in 2018 due to central regulations that were always late and frequently changed so that the stipulation of the Regent's Regulation which should have been set before November was not per with expectations. The Implications of the Delay in the Regent's Regulation on Financial Management of Village Fund Allocations and Village Funds greatly impact villages in Luwu such as village government activities in carrying out government, development, and community services.